PROBLEMS AND SOLUTIONS IN INCREASING THE ECONOMIC COMPETENCE OF THE AGRICULTURAL NETWORK - Aliqulov D. (Journal of new century innovations, 2023)
Annotation: The agriculture industry is an integral part of our global economy and society, providing food, fiber, and other essential products. As the world's population continues to grow, the demand for agricultural products is increasing at an unprecedented rate. To meet this demand sustainably, the industry must embrace innovative practices such as intelligent agriculture.